2014
DOI: 10.2139/ssrn.2507936
|View full text |Cite
|
Sign up to set email alerts
|

Recent Estimates of Exchange Rate Pass-Through to Import Prices in the Euro Area

Abstract: This paper provides an update on the exchange rate pass-through (ERPT) estimates for 12 euro area (EA) countries. First, based on quarterly data over the 1990-2012 period, our study does not find a significant heterogeneity in the degree of pass-through across the monetary union members, in contrast to previous empirical studies. As we use a longer time span for the post-EA era than existing studies, this is not surprising, since the process of monetary union has entailed some convergence towards more stable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…These values are lower than the average exchange rate elasticity of 0.54 reported by Ben Cheikh and Rault (2016) for twelve euro area countries in the period 1990Q3-2012Q4, and also lower than the average of 0.47 for eighteen low-inflation countries in the period 1992-2012, estimated by Ben Cheikh and Louhichi (2016). Thus our results provide further evidence that ERPT has been declining over time, as found in the recent literature (Campa and Goldberg 2005;Ben Cheikh and Rault 2016). This may be attributed to the fact that our data comprises a longer period since the creation of the monetary union, so that a greater degree of convergence to more stable macroeconomic conditions has taken place in most countries of the panel.…”
Section: Discussionsupporting
confidence: 85%
“…These values are lower than the average exchange rate elasticity of 0.54 reported by Ben Cheikh and Rault (2016) for twelve euro area countries in the period 1990Q3-2012Q4, and also lower than the average of 0.47 for eighteen low-inflation countries in the period 1992-2012, estimated by Ben Cheikh and Louhichi (2016). Thus our results provide further evidence that ERPT has been declining over time, as found in the recent literature (Campa and Goldberg 2005;Ben Cheikh and Rault 2016). This may be attributed to the fact that our data comprises a longer period since the creation of the monetary union, so that a greater degree of convergence to more stable macroeconomic conditions has taken place in most countries of the panel.…”
Section: Discussionsupporting
confidence: 85%
“…We point out that import‐price pass‐through elasticities are in some extent heterogeneous across our sample of EA countries. This pattern is in line with the recent literature on ERPT in the currency union members (see, e.g., Ben Cheikh & Rault, ).…”
Section: A Sectoral Analysis Of the Pass‐throughsupporting
confidence: 92%
“…For a certain threshold, the change in economic development will increase the level of passthrough ratio. Cheikh and Rault argued that there is a threshold effect for spreads and exchange rates. Winkelried suggested that the stable and low‐inflation economic environment may impair the portion of price adjustment caused by exchange rate volatility.…”
Section: Literature Reviewsmentioning
confidence: 99%